NISSIM AMZALLAG, Esau in Jerusalem: The Rise of a Seirite Religious Elite in Zion in the Persian Period. Cahiers de la Revue Biblique 85. Pendé, J. Gabalda et Cie, 2015. ISBN 978–2–85021–242–0. Paperback 62,00 € - Gruber, Mayer I. (2015)
Fil: Gruber, Mayer I. Ben-Gurion University of the Negev; Israel